2002
DOI: 10.1111/j.1744-6570.2002.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rotated Leadership and Peer Evaluation on the Functioning and Effectiveness of Self‐managed Teams: A Quasi‐experiment

Abstract: In a quasi‐experiment of 38 self‐managed undergraduate teams, we examined the effects of team designs that differed with respect to the form of member evaluation and team leadership. Relative to teams that relied on external evaluations, teams with peer evaluations had higher levels of workload sharing, voice, cooperation, performance, and member satisfaction. Relative to teams that relied on leader emergence, teams that rotated leadership among members had higher levels of voice, cooperation, and performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 56 publications
5
144
1
1
Order By: Relevance
“…Quando os membros da equipe adotam comportamentos de suporte (ajudam os novos colegas de trabalho a tornarem-se mais produtivos) aumentam a eficácia do grupo de trabalho ou da unidade (MacKenzie, Podsakoff, & Fetter, 1993), na medida em que possibilitam a transferência de conhecimento no seio organizacional (Koning & Van Kleef, 2015). Os membros da equipe podem completar as respectivas tarefas, que dificilmente realizariam de forma individual, através do apoio mútuo, promovendo não só a integração das suas contribuições (Erez, Lepine, & Elms, 2002), como também a melhoria do desempenho da equipe (Campion, Medsker, & Higgs, 1993).…”
Section: Comportamentos De Suporte E Eficácia Grupalunclassified
“…Quando os membros da equipe adotam comportamentos de suporte (ajudam os novos colegas de trabalho a tornarem-se mais produtivos) aumentam a eficácia do grupo de trabalho ou da unidade (MacKenzie, Podsakoff, & Fetter, 1993), na medida em que possibilitam a transferência de conhecimento no seio organizacional (Koning & Van Kleef, 2015). Os membros da equipe podem completar as respectivas tarefas, que dificilmente realizariam de forma individual, através do apoio mútuo, promovendo não só a integração das suas contribuições (Erez, Lepine, & Elms, 2002), como também a melhoria do desempenho da equipe (Campion, Medsker, & Higgs, 1993).…”
Section: Comportamentos De Suporte E Eficácia Grupalunclassified
“…However, emergent leadership often leads to feelings of reduced responsibility by the leader and the team members which may lead to reductions in effort toward achieving team outcomes (Shepperd, 1993). Erez, Lepine, and Elms (2002) have suggested that rotated leadership within teams will help ameliorate reduced responsibility by fostering a sense of workload sharing and empathy.…”
Section: Theory and Propositionsmentioning
confidence: 99%
“…Within these teams, decision-making authority is left to the members who belong to that team. Additionally, self-managed teams allow for various configurations of team processes such as leadership (Erez, Lepine, & Elms, 2002). In one instance, a leader within the team may emerge and carry out leadership functions (Karakowsky & Siegel, 1999;Plowman et al, 2007).…”
Section: Theory and Propositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These scales generally identify a range of positive teaming behaviors, and students use a Likert scale to describe their peers' performance for each of them. 9,22 Criteria generally used for peer evaluations include: commitment to the group, ability to deal constructively with conflicts (communication), active participation in decision making, accountability for assigned tasks, and assumption of initiative or a leadership role. 10 In a meta-analysis of peer rating instruments, Baker identified eight basic components 2 1.…”
Section: Peer Assessments Of Teamworkmentioning
confidence: 99%